Isolation and Characterization of phiLLS, a Novel Phage with Potential Biocontrol Agent against Multidrug-Resistant Escherichia coli - Amarillas, Luis; Rubí-Rangel, Lucia; Chaidez, Cristobal; González-Robles, Arturo; Lightbourn-Rojas, Luis; León-Félix, Josefina (Frontiers in Microbiology, 2017)
Foodborne diseases are a serious and growing problem, and the incidence and prevalence of antimicrobial resistance among foodborne pathogens is reported to have increased. The emergence of antibiotic-resistant bacterial strains demands novel strategies to counteract this epidemic. In this regard, lytic bacteriophages have reemerged as an alternative for the control of pathogenic bacteria. However, the effective use of phages relies on appropriate biological and genomic characterization. In this study, we present the isolation and characterization of a novel bacteriophage named phiLLS, which has shown strong lytic activity against generic and multidrug-resistant Escherichia coli strains. Transmission electron microscopy of phiLLS morphology revealed that it belongs to the Siphoviridae family. Furthermore, this phage exhibited a relatively large burst size of 176 plaque-forming units per infected cell. Phage phiLLS significantly reduced the growth of E. coli under laboratory conditions. Analyses of restriction profiles showed the presence of submolar fragments, confirming that phiLLS is a pac-type phage. Phylogenetic analysis based on the amino acid sequence of large terminase subunits confirmed that this phage uses a headful packaging strategy to package their genome. Genomic sequencing and bioinformatic analysis showed that phiLLS is a novel bacteriophage that is most closely related to T5-like phages. In silico analysis indicated that the phiLLS genome consists of 107,263 bp (39.0 % GC content) encoding 160 putative ORFs, 16 tRNAs, several potential promoters and transcriptional terminators. Genome analysis suggests that the phage phiLLS is strictly lytic without carrying genes associated with virulence factors and/or potential immunoreactive allergen proteins. The bacteriophage isolated in this study has shown promising results in the biocontrol of bacterial growth under in vitro conditions, suggesting that it may prove useful as an alternative agent for the control of foodborne pathogens. However, further oral toxicity testing is needed to ensure the safety of phage use.